Empowering women with digital solutions: Leveraging the potential of the private sector for socio-technical innovation - Ketema, Dessalegn Molla; Nchanji, Eileen Bogweh; Endrias, Abrham (2023)
The Gender Equality Initiative (HER+) conducts innovative gender and social science research to develop actionable solutions to enhance climate resilience and the empowerment of women in Africa and Asia. As there is no one-size-fits-all solution to these challenges, HER+ identifies and models diverse scenarios for co-creation of socio-technical innovations. According to Barret et al 2022, co-creation of bundled approaches is essential to enable new technologies and practices to emerge, adapt, and be upscaled within and across diverse contexts. The co-creation of socio-technical innovation bundles requires multi-stakeholder cooperation among public and private sector organizations.